WHAT IS INTERIORITY AND WHY MIGHT IT BE IMPORTANT FOR HUMAN PERFORMANCE TECHNOLOGY?. Issue 3 (March 2014) - Leonard, Hugh
<x xml:space="preserve">Abstract</x> Considerations of the inner world of workers and organizations might not fall within the provenance of human performance technology (HPT) practitioners. However, when it comes to being creative, workers need fertile imaginations driven from within. When it comes to productivity, mostly inner energies drive collaboration. When it comes to results, leaders must nurture workers toward wholeness for effective decisions and wisdom‐driven action. For these reasons, HPT practitioners need to know how to engage with the interiority factor.